2021
DOI: 10.1007/s00540-021-02909-9
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine ameliorates lipopolysaccharide-induced acute lung injury by inhibiting the PI3K/Akt/FoxO1 signaling pathway

Abstract: Purpose Dexmedetomidine (DEX) has been associated with inflammation, oxidative stress, and apoptosis, but its effects on lipopolysaccharide (LPS)-induced lung injury remain uncertain. The present study explored the effects of DEX on LPS-induced lung injury and studied the possible molecular mechanisms by testing the effects of the phosphoinositide-3 kinase (PI3K) inhibitor LY294002 and BEZ235. Methods Seventy C57BL/6 mice were randomly divided into the control, LPS, LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…[64–66] In addition, LPS-induced acute lung injury, including lung inflammation, oxidative stress, and apoptosis, could be prevented by inhibiting the PI3K/Akt/FoxO1 signaling pathway. [67] These findings are consistent with our view that the PI3K/Akt signaling pathway is more important in the involvement of RDF against AP.…”
Section: Discussionsupporting
confidence: 92%
“…[64–66] In addition, LPS-induced acute lung injury, including lung inflammation, oxidative stress, and apoptosis, could be prevented by inhibiting the PI3K/Akt/FoxO1 signaling pathway. [67] These findings are consistent with our view that the PI3K/Akt signaling pathway is more important in the involvement of RDF against AP.…”
Section: Discussionsupporting
confidence: 92%
“…It shows that the protective effect of DEX is closely related to the inhibition of inflammation. However, the mechanism by which DEX inhibits the inflammatory response has not been elucidated [16][17][18]. Studies have shown that DEX can regulate signaling pathways and genes associated with inflammation through interactions with several miRNAs [19].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated Foxo1 could be dephosphorylated to form Foxo1 once AKT is activated, leading to its nuclear translocation [ 45 ]. It has been demonstrated that both the activation of the AKT and the reduction of Foxo1 expression in the nucleus can give rise to lung pathological injury and ARDS [ 18 ]. Here, we found that LPS stimulation significantly promoted the phosphorylation of AKT and the dephosphorylation of Foxo1 in macrophages and lung tissues from mice with ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…AKT/Foxo1 signaling pathway possesses multiple regulators as well as effectors including glucose, insulin, cytokines, and growth factors, displaying significant functions in cell survival, metabolism, inflammation, and oxidative stress [13][14][15][16]. Previous studies have demonstrated that changes in AKT activity levels in macrophages show significant impacts on polarization and activation of macrophages via regulating Foxo1 activity during ARDS [17,18]. Hence, AKT/Foxo1 pathway may be a critical signaling target in drug discovery and treatment of ARDS.…”
Section: Introductionmentioning
confidence: 99%